2016
DOI: 10.3748/wjg.v22.i2.823
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Wnt/β-catenin pathway in hepatocellular carcinoma treatment

Abstract: Hepatocellular carcinoma (HCC) is one of the most common causes of cancer-related death worldwide. Liver cancer is generally related to hepatitis B or C infection and cirrhosis. Usually, patients with HCC are asymptomatic and are diagnosed at late stages when surgical treatment is no longer suitable. Limited treatment options for patients with advanced HCC are a major concern. Therefore, there is an urge for finding novel therapies to treat HCC. Liver cancer is highly heterogeneous and involved deregulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
203
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(210 citation statements)
references
References 74 publications
5
203
0
2
Order By: Relevance
“…Furthermore, hypoxic microenvironment will affect cell proliferation, angiogenesis, invasion and metastasis of tumors [9][10][11]. Studies have shown that Wnt/β-catenin signaling pathway is involved in the proliferation, differentiation, metastasis and invasion of tumor cells [12,13], but no literature has reported the effect of Wnt/β-catenin signaling pathway on the proliferation, invasion and metastasis of NSCLC A549 cells under the hypoxic environment. Thus, in this study, we aimed to investigate the potential mechanism of Wnt/β-catenin signaling pathway through discovering the effects of Wnt/β-catenin signaling pathway on NSCLC A549 cell proliferation and invasion under the hypoxic microenvironment in an in-vitro experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hypoxic microenvironment will affect cell proliferation, angiogenesis, invasion and metastasis of tumors [9][10][11]. Studies have shown that Wnt/β-catenin signaling pathway is involved in the proliferation, differentiation, metastasis and invasion of tumor cells [12,13], but no literature has reported the effect of Wnt/β-catenin signaling pathway on the proliferation, invasion and metastasis of NSCLC A549 cells under the hypoxic environment. Thus, in this study, we aimed to investigate the potential mechanism of Wnt/β-catenin signaling pathway through discovering the effects of Wnt/β-catenin signaling pathway on NSCLC A549 cell proliferation and invasion under the hypoxic microenvironment in an in-vitro experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β-catenin signaling activation is commonly activated in a wide variety of cancers [10,12], including HCC [13,14]. The mechanism of β-catenin activation in HCC involves mutations of the β-catenin gene,whichare noted in around 19% of all cases [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of these genes via hypermethylation of their promoters has been shown to be part of the pathogenesis in a plethora of human malignancies. [1][2][3][4][5][6] Aberrant regulation of the Wnt signaling pathway is known to play a role in tumorigenesis and maintenance of cancer stem cells. 3,4,28 The Wnt pathway can be activated aberrantly not only by mutations of genes functioning in Wnt signaling such as APC and CTNNB1 but also by dysregulation of secreted antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Wnt/β-catenin signaling has pivotal roles both in early developmental stages and in tissue maintenance of adults. The pathway operates by regulating specific genes that function in cell fate, proliferation, polarity, migration, and differentiation.…”
Section: Introductionmentioning
confidence: 99%